Heterogeneous Ice Nucleation Ability of NaCl and Sea Salt Aerosol Particles at Cirrus Temperatures. Issue 5 (10th March 2018) - Wagner, Robert; Kaufmann, Julia; Möhler, Ottmar; Saathoff, Harald; Schnaiter, Martin; Ullrich, Romy; Leisner, Thomas
Abstract: In situ measurements of the composition of heterogeneous cirrus ice cloud residuals have indicated a substantial contribution of sea salt in sampling regions above the ocean. We have investigated the heterogeneous ice nucleation ability of sodium chloride (NaCl) and sea salt aerosol (SSA) particles at cirrus cloud temperatures between 235 and 200 K in the Aerosol Interaction and Dynamics in the Atmosphere aerosol and cloud chamber. Effloresced NaCl particles were found to act as ice nucleating particles in the deposition nucleation mode at temperatures below about 225 K, with freezing onsets in terms of the ice saturation ratio, S ice, between 1.28 and 1.40. Above 225 K, the crystalline NaCl particles deliquesced and nucleated ice homogeneously. The heterogeneous ice nucleation efficiency was rather similar for the two crystalline forms of NaCl (anhydrous NaCl and NaCl dihydrate). Mixed‐phase (solid/liquid) SSA particles were found to act as ice nucleating particles in the immersion freezing mode at temperatures below about 220 K, with freezing onsets in terms of S ice between 1.24 and 1.42. Above 220 K, the SSA particles fully deliquesced and nucleated ice homogeneously. Ice nucleation active surface site densities of the SSA particles were found to be in the range between 1.0 · 10 10 and 1.0 · 10 11  m −2 at T  < 220 K. These values are of the same order of magnitude as ice nucleation active surface site densities recently determined for desert dust, suggesting a potential contribution of SSA particles to low‐temperature heterogeneous ice nucleation in the atmosphere. Key Points: Mixed‐phase (solid/liquid) inorganic sea salt aerosol particles activate heterogeneous ice nucleation via immersion freezing below 220 K Heterogeneous ice nucleation efficiency is similar for the two crystalline forms of NaCl (anhydrous NaCl and NaCl dihydrate) Ice nucleation active surface site densities of the sea salt aerosol particles are comparable in magnitude to those of desert dust